Interleukin‐10 Gene Promoter and NFKB1 Promoter Insertion/Deletion Polymorphisms in Systemic Sclerosis. (24th January 2013) - Salim, P. H.; Jobim, M.; Bredemeier, M.; Chies, J. A. B.; Brenol, J. C. T.; Jobim, L. F.; Xavier, R. M.
Abstract Systemic sclerosis (SSc) is a connective tissue disease characterized by fibrotic, immunological and vascular abnormalities. Nuclear factor‐kB (NFKB), as a key transcription factor involved in the regulation of immune responses, appears to be a good candidate for studies on the pathogenesis of autoimmune diseases, as well as the interleukin‐10 (IL‐10) polymorphism, which other studies have suggested an association with SSc. Our objective was to study the association of NFKB and IL‐10 gene polymorphisms with SSc. One hundred and fifty‐one SSc patients and 147 healthy bone marrow donors were enrolled in a case–control study. Blood was collected for DNA extraction; typing of IL‐10 genes was made by polymerase chain reaction with sequence‐specific primers (PCR–SSP), and NFKB gene typing was made by restriction fragment length polymorphism (RFLP). Patients underwent clinical evaluation, serology, Doppler echocardiography and chest high‐resolution computed tomography. The frequency of IL‐10 (−1082) GG genotype was found to be significantly higher in SSc patients (36.4%) as compared to healthy controls (22.4%) (P = 0.012). The frequency of heterozygous genotype GA was significantly lower (P = 0.004) in patients (38.4%) in comparison with control subjects (55.8%). A predominance of the high‐producing IL‐10 phenotype (GCC+/GCC+) was observed in SSc patients compared with healthy controls (37.7% versus 24.5%, respectively; OR: 1.87, 95% CI: 1.10–3.19, P = 0.019). No significant difference was found in the allelic and genotype distribution of the NFKB promoter polymorphism between patients and controls. No statistically significant associations were found between IL‐10 or NFKB polymorphisms clinical and laboratory features of SSc. Our results confirmed the association of the high‐producing phenotype (GCC+/GCC+) with increased risk for SSc, but found no correlation with NFKB polymorphisms.